Antcin K, a Triterpenoid Compound from Antrodia camphorata, Displays Antidiabetic and Antihyperlipidemic Effects via Glucose Transporter 4 and AMP-Activated Protein Kinase Phosphorylation in Muscles. (8th May 2016) - Kuo, Yueh-Hsiung; Lin, Cheng-Hsiu; Shih, Chun-Ching; Yang, Chang-Syun
Abstract : The purpose of this study was to screen firstly the potential effects of antcin K (AnK), the main constituent of the fruiting body of Antrodia camphorata, in vitro and further evaluate the activities and mechanisms in high-fat-diet- (HFD-) induced mice. Following 8-week HFD-induction, mice were treated with AnK, fenofibrate (Feno), metformin (Metf), or vehicle for 4 weeks afterward. In C2C12 myotube cells, the membrane GLUT4 and phospho-Akt expressions were higher in insulin and AnK-treated groups than in the control group. It was observed that AnK-treated mice significantly lowered blood glucose, triglyceride, total cholesterol, and leptin levels in AnK-treated groups. Of interest, AnK at 40 mg/kg/day dosage displayed both antihyperglycemic effect comparable to Metf (300 mg/kg/day) and antihypertriglyceridemic effect comparable to Feno (250 mg/kg/day). The combination of significantly increased skeletal muscular membrane expression levels of glucose transporter 4 (GLUT4) but decreased hepatic glucose-6-phosphatase (G6 Pase) mRNA levels by AnK thus contributed to a decrease in blood glucose levels. Furthermore, AnK enhanced phosphorylation of AMP-activated protein kinase (phospho-AMPK) expressions in the muscle and liver. Moreover, AnK treatment exhibited inhibition of hepatic fatty acid synthase (FAS) but enhancement of fatty acid oxidation peroxisome proliferator-activated receptor α (PPAR α ) expression coincident with reduced sterol response element binding protein-1c (SREBP-1c) mRNA levels in the liver may contribute to decreased plasma triglycerides, hepatic steatosis, and total cholesterol levels. The present findings indicate that AnK displays an advantageous therapeutic potential for the management of type 2 diabetes and hyperlipidemia.